2016
DOI: 10.1177/0022219415624101
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trait Anxiety and Preoccupation With Reading Disabilities of Children and Their Mothers in Predicting Children’s Reading Comprehension

Abstract: This study investigated the relationship between reading comprehension (RC), trait anxiety, and preoccupation with reading disability (RD) in 88 school children in Grades 3 through 5 and in their mothers. Children's trait anxiety had a significant direct negative relationship with RC and also mediated the association between preoccupation with RD and RC. Mothers' preoccupation with their children's RDs had a direct negative association with their children's RC. This association was also mediated through childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…A central symptom of anxiety is being preoccupied with personal thoughts or emotions both of which can lead to mind wandering (Smallwood et al, 2007;Unsworth & McMillan, 2013). Similar to mind-wandering, trait-based anxiety can interfere with inference-making and reading comprehension (Blicher et al, 2017;Gygax et al, 2007). In addition, higher levels of anxiety are associated with lower working memory capacity, which can interfere with attention to, processing of, and retention of the text (Albano et al, 2003).…”
Section: Student Characteristics That Affect Attention During Readingmentioning
confidence: 99%
“…A central symptom of anxiety is being preoccupied with personal thoughts or emotions both of which can lead to mind wandering (Smallwood et al, 2007;Unsworth & McMillan, 2013). Similar to mind-wandering, trait-based anxiety can interfere with inference-making and reading comprehension (Blicher et al, 2017;Gygax et al, 2007). In addition, higher levels of anxiety are associated with lower working memory capacity, which can interfere with attention to, processing of, and retention of the text (Albano et al, 2003).…”
Section: Student Characteristics That Affect Attention During Readingmentioning
confidence: 99%
“…In other studies, mental health was not included as an outcome variable. Rather, the relative influence of learning difficulties and/or behaviour/mental health on children’s social skills [ 62 ] or academic outcomes was investigated (e.g., grades, reading comprehension, secondary school completion), see for example [ 43 , 57 , 63 , 64 ]. However, in our estimation, the aim of 39 (40%) of the included studies aligned to that of this review; that is, the researchers aimed to better understand mental health in the context of childhood learning/reading difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Negative responses indicate that the disability is stigmatized (see Author). In adopting this definition, future studies should focus on determining maternal perceptions of public stigma toward LD, as well of the levels of courtesy stigma they experience (for a measure of a similar construct, namely, mothers’ preoccupation with children’s reading disabilities, see Blicher et al, 2017). Moreover, future research should also focus on the associations between these types of stigma and mothers’ reactions toward their children.…”
Section: Discussionmentioning
confidence: 99%
“…Since research showed that mothers’ behaviors and children with LD’s academic performance are connected (?) (e.g., see Blicher et al, 2017; Stone et al, 2002), this outcome should also be examined more extensively.…”
Section: Discussionmentioning
confidence: 99%